Bismuth oxychloride clusters prepared by ball-milling technique and their multifunctional application in potassium ion storage and photodegradation. (October 2022) - Wu, Jingjing; Zhang, Lida; Yan, Zhongyuan; Wen, Jinquan; Chang, Jing; Zhang, Yifan; Bai, Ling; Li, Ziquan; Huang, Zhen-Dong
Abstract: BiOCl is a promising anode material for potassium ion batteries and also one of the potential candidate catalysts for photocatalytic degradation of organic pollutants. Here, a wet ball-milling assisted hydrolysis method is proposed to produce the desired BiOCl. During the hydrolysis process under the ball-milling condition, the obtained BiOCl nanosheets self-assemble into flower-like micro-clusters with a uniform distribution of Bi 3+, O 2−, Cl − and a low BET specific surface area. Especially, the obtained BOCl clusters demonstrate a superior potassium ion storage performance over most of the reported BiOCl and comparable photocatalytic degradation properties of Rhodamine B. The charge capacity of BiOCl electrodes retained 373 mAhg −1 after 300 cycles at 100 mAg −1 and 232 mAhg −1 after 1000 cycles at 500 mAg −1, respectively. ∼96.7% RhB in the aqueous solution can be degraded after 60 min of light irradiation under a 300 W xenon lamp. Graphical abstract: Flower-like Nanosheet clusters of multifunctional BiOCl is massively produced by applying the ball-milling-assisted hydrolysis strategy. The as-prepared BiOCl clusters demonstrate a superior potassium ion storage performance over most of the reported BiOCl and comparable photocatalytic degradation properties of Rhodamine B (RhB). Image, graphical abstract